Enhancing English Language Teaching Pedagogy in a Multimedia Course for Pre-Service Teachers - FALASCA, MARINA (American Journal of STEM Education, 2024)
This article explores the integration of differentiated instruction (DI) and universal design for learning (UDL) principles in a preservice EFL teacher training programme. The author discusses strategies for designing course content, materials, activities, and assessments that accommodate diverse learning styles, preferences, and abilities. These strategies are illustrated through a case study example that outlines the practical implementation of DI and UDL principles in a multimedia course for preservice EFL teachers in Argentina. The article concludes by emphasizing the importance of integrating these pedagogical approaches to promote inclusive teaching practices and optimize learning outcomes in English language teaching contexts.